Revisiting Student Self-Improvement - Vladimirovna Kryucheva, Yana; Vasilevna Tolstoukhova, Irina; Ilinichna Iakobiuk, Liubov; Vladimirovna Vinogradova, Marina (International Journal of Engineering and Technology, 2018)
This paper substantiates the relevance of cultivating the need for self-improvement in students at technical colleges.The authors identify several types of self-improvement and explore their key features. The findings from the authors’ psychological/pedagogical study help identify three major levels of self-development.To determine students’ self-improvement development levels, the authors employed such research methods as survey by questionnaire, testing, interview, observation, and analysis of activity outcomes.Using the diagnostic method and on the strength of sociological data obtained as part of the study, the authors developed a program consisting of two modules aimed at the deliberate and purposeful cultivation of the need for self-improvement, development of one’s volitional qualities of character, nourishing of the ability to self-regulate one’s behavior, and fostering of the ability to pursue meaningful life goals.The findings of this study may be of interest to instructors, teachers, and postgraduate students interested in the development and implementation of competency-based learning within the nation’s system of higher education.